Low switched memory B cells are associated with no humoral response after SARS-CoV-2 vaccine boosters in kidney transplant recipients - Seija, Mariana; García-Luna, Joaquin; Rammauro, Florencia; Brugnini, Andreína; Trías, Natalia; Astesiano, Rossana; Santiago, José; Orihuela, Natalia; Zulberti, Catherine; Machado, Danilo; Recalde, Cecilia; Yandián, Federico; et al. (Frontiers in Immunology, 2023)
Introduction: Humoral response after SARS-CoV-2 vaccination and boosters in kidney transplant recipients (KTR) is heterogeneous and depends on immunosuppression status. There is no validated immune measurement associated with serological response.Multicolor flow cytometric immunophenotyping could be useful to measure immune response. This work aimed to study B and T cell compartments by Standardized EuroFlow PID Orientation after SARS-CoV-2 vaccination and its association with IgG SARS-CoV-2 seropositivity status after 2 doses or boosters.Methods: We conducted a multicenter prospective study to evaluate humoral response after SARS-CoV-2 vaccination in KTR. Heterologous regimen: 2 doses of inactivated SARS-CoV-2+2 boosters of BNT162b2 mRNA (n=75). Homologous vaccination: 2 doses of BNT162b2 mRNA+one BNT162b2 mRNA booster (n=13). Booster doses were administrated to KTR without taking into account IgG SARS-CoV-2 seropositivity status. Peripheral blood samples were collected 30 days after the second dose and after the last heterologous or homologous booster. Standardized EuroFlow PID Orientation tube (PIDOT) and a supervised automated analysis were used for immune monitoring of cellular subsets after boosters.Results: 88 KTR were included and divided into 3 groups according to the time of first detected IgG SARS-CoV-2 seropositivity: non-responders (NR, n=23) boosters' responders (BR, n=41), and 2 doses responders (2DR, n=24). NR group was more frequent on mycophenolate than the responder groups. (NR:96%, BR:80%, 2DR:42%, p=0.000). Switched memory B cells in the 2DR group were higher compared to BR and NR groups (median 30, 17 and 10 cells/ul, respectively p =0,017). Central memory/Terminal Memory CD8 T cells absolute count was also higher in the 2DR group compared to BR and NR groups. (166, 98, and 93 cells/ul, respectively p=0.041). The rest of the T cell populations studied did not show a statical difference.In conclusion, switched memory B cells and memory CD8 T-cell populations in peripheral blood were associated with the magnitude of the humoral response after SARS-CoV-2 vaccination. Boosters increased IgG anti-SARS-CoV-2 levels, CM/TM CD8 T cells, and switched MBCs in patients with seropositivity after 2 doses. Interestingly, no seropositivity after boosters was associated with the use of mycophenolate and a lower number of switched MBC and CM/TM CD8 T cells in peripheral blood.